Analysis of the Reasons for the Judge's Decision Which Relieves Defendants in Corruption Cases - Yogi prasetyo; Ferry Irawan Febriansyah; Alfalachu Indiantoro; Aries Isnandar; Ucuk Agiyanto (Universitas Muhammadiyah Surakarta, 2022)
Purpose of the study: This research article aims to explain the analysis of several reasons for the judge's decision which is considered to lighten the defendant in corruption cases in Indonesia. Methodology: This study used a normative research method with a philosophical approach. Results: The results of this study indicate that judges continue to impose light sanctions on state officials who are accused of corruption cases for various reasons that can be taken into consideration. The following is an analysis of some of these reasons: have never been punished; be honest and be kind; have family responsibilities; refund corrupted money; incorrect application of the law; have no authority; motivated by other people; have a sense of justice; serve the community; get public scorn; and refrain from engaging in corrupt behavior. Applications of this study: Theoretically, academics can use this research to add and develop their knowledge of the law. As for practitioners, especially judges, this research can be used as material for conclusions and considerations when making decisions in corruption cases, so that efforts to eradicate corruption can definitely be achieved. Novelty/Originality of this study: The corruption issue in Indonesia is influenced by the judge's decision in addition to the country’s bad bureaucratic culture. The low judge's decision on corruption cases can also affect the number of state officials who commit acts of corruption. Several reasons that could influence the judge's decision to reduce the corruptors’ sentences. In order to find a true legal truth, it would be useful to study the judge’s reasoning for reducing the corruptor’s punishment because the judge's decision is the most decisive stage in the legal status and fate of the defendant. This is why it is critical to do a more in-depth review of the law in order to ensure that it continues to operate as intended